The Coronavirus Chasm in Inflammatory Bowel Disease: Report of Patient-Centered Care at a Hospital in Northern Portugal - Lago, Paula (GE Port J Gastroenterol, 2021)
INTRODUCTION: Although patient-centered care can be found in the mission statement of nearly every hospital, it is not always put into practice, and COVID-19 brings new challenges even to the best-organized hospitals and well-developed health care systems. METHODS: In the current COVID-19 pandemic, inflammatory bowel disease (IBD) patients have a potentially higher risk of complications from this infectious disease due to the use of immunosuppressant and/or biologic treatments and due to flares of this chronic illness, which often require urgent care and sometimes hospitalization. Moreover, patients undergoing biologic intravenous (IV) treatment visit the hospital for scheduled IV infusions. DISCUSSION: In hospitals like ours, where COVID-19 patients are treated, the organization of “clean circuits” is essential to minimize the risks of infection for non-COVID-19 patients, such as patients in IBD infusion units. In our hospital, the IBD infusion unit is located within the gastroenterology department, which, under normal circumstances, is very advantageous for patients but in the current context is not. Our goal was to maximize adherence to biologic IV treatment and clinical safety at a time of profound changes in gastroenterology activity and in a department with daily increases in the number of COVID-19 patients. CONCLUSION: To this end, we initiated proactive COVID-19 testing in IBD patients undergoing biologic IV treatment and changed the location of the infusion unit to a “COVID-free” institution, maintaining the care of these patients by the dedicated IBD team of our department. The purpose of this report is to show that a patient-centered care strategy allowed us to reach very high levels of patient comfort, satisfaction, and compliance with therapeutics.